Interest Free Banking in Ethiopia: Customer Awareness, Satisfaction and its Role on Economic Development - Debebe Alemu Kebede (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study is aimed at evaluating the customer’s awareness and satisfaction toward Interest-free Banking and its role on Ethiopia economic development with some selected Commercial Bank in Ethiopia. This method achieves the aim of the study the primary data was collected from Customers and Managers of the selected banks by using convenience method through questionnaire and interview. While, secondary data was collected by compiling and summarizing the bank’s Annual reports and Journals. The collected data was analyzed in descriptive and inferential analysis. The finding of the study depicts as low customer awareness regarding Interest-free Banking services except the Interest-free Banking account holders. Further, majority of Interest-free Banking account holders are more or less satisfied with the current Interest-free Banking services provided since, it can potentially serve as an alternative banking channel in filling the gap left unaddressed by conventional banking and economic development in relation to idle monetary resource mobilization and allocation, inviting to use banking system, creating employment opportunity, supporting GDP growth and assisting in stabilizing crisis and arresting inflation. Impact on the study result as Interest Free Banking have its own role on the country economic development through mobilizing the idle monitory resource, allocating the monitory resource, creating employment opportunity, and inviting to the banking system. it recommended as the banks should make aggressive promotion for customers out of Muslim customers, the government has to support and should give more emphasis to enable Interest Free Banking service, promote Interest Free Banking which can help assist the economy in stabilizing economic crisis and arresting inflation.